Development of Arabic Language Learning Evaluation Media Through Wordwall Education Games for Year 8 Junior High School Student Pecangakan, Pemalang - Muasomah; Khadiqoh, Nailil; Dzulkifli M. Mooduto; Moh. Nurul Huda (Naatiq: Journal of Arabic Education, 2025)
Previous studies on Arabic language learning evaluation have shown that many schools still rely on traditional assessment methods, which often fail to comprehensively measure students’ actual learning competencies. Research on digital-based evaluation tools also indicates that interactive learning media can significantly enhance student engagement and performance compared to conventional paper-based test. Motivated by these findings, this research addresses the issue of Arabic language learning evaluation at Asy-Syafi’iyah Junior High School, which still predominantly uses written tests with paper media. Therefore, this study aims to develope an evaluation media for Arabic language learning using Wordwall educational games as an alternative assessment tool for Grade 8 students. This research employs the ADDIE development model, which consists of  five stages: Analysis, Design, Development, Implementation, and Evaluation. Data were collected through interviews, questionnaires, expert validation sheets, and learning outcome test. The findings show that the Word wall-based evaluation media achieved high validity score from content and media experts, indicating its appropriateness for classroom application. During implementation, students demonstrated higher engagement, lower anxiety, and improved test results compared to traditional evaluation methods. The evaluation result further confirm that the media is effective, user-friendly, and suitable as an alternative tool for assessing Arabic Learning outcome.  In conclusion, the develop Word wall educational games serve a valid, practical, and effective evaluation medium for Arabic language learning. This innovation supports the integration of technology and interactive assessment in line with the demands of modern education.